Photodynamic Therapy: The Development of New Photosensitisers - Wainwright, Mark (Anti-Cancer Agents in Medicinal Chemistry, 2008)
The first 20 years of anticancer photodynamic therapy (PDT) were based on the utility of the oligomeric mixture haematoporphyrin derivative (HpD) in various forms. More recently new derivatives have become available, both porphyrin-derived and employing new chromophores, for example from the phthalocyanine and phenothiazinium families. In addition, a major research effort has been rewarded with the clinical acceptance of the porphyrin precursor 5-aminolaevulinic acid (ALA). New photosensitisers intended for clinical use must exhibit advantageous drug performance profiles compared to the first-generation porphyrin derivatives. This can be seen, in vitro, in improved photophysical properties such as the extension of the useful light absorption spectrum into the near infrared - offering greater tissue penetration - as well as in the synthesis of pure compounds rather than mixtures. In this review, recent developments in photosensitiser families are discussed with respect to in vitro performance indicators and to potential application in oncology.
Keywords: aminolaevulinic acid